Electrochemically Non-Enzymatic Urea Estimation in Human Dialysate Waste Using Indirect NiOOH-Urea Oxidation - Janyasupab M. (2023)
Non-enzymatic urea detection in human dialysate offers a sustainable and spontaneous platform for advanced analysis and monitoring. This study investigated urea estimation in dialysate by using an indirect urea oxidation of nickel on nitrogen doped carbon with an incorporation of surface roughness (Rf) and double layer current (Idl). Fascinatingly, the second oxidation peak on (reverse) cathodic scan at 0.42 V vs Ag/AgCl in cyclic voltammetry and the first peak of differential pulse voltammetry (DPV) after background subtraction were evidenced to the exploited NiOOH binding with urea, concurrently with the regeneration of Ni(OH)2. In presence of more urea, the decreasing trends of the oxidation peaks in both techniques were observed and capable of determining urea concentrations in human dialysate. In consideration of actual reaction current, the measured total current after background subtraction in fresh simulated dialysate provides the sensitivity of −5.136 × 10−5 A.mM−1 (R2 = 0.998) and limit of detection of 60.2 μM in 1-5 mM linear range. For validation in patients’ dialysate, the total current peak was normalized by Rf and subtracted from Idl, resulting in excellent urea estimation with recovery percentage between 99.18 and 102.68 in comparison to that of clinical standard, offering future prognostic monitoring and wearable artificial kidney.